Decrease of nuclear reactivity to growth-regulatory galectin-1 in senescent human keratinocytes and detection of non-uniform staining profile alterations upon prolonged culture for galectin-1 and -3 - Chovanec, M; Smetana, K; Dvoránková, B; Plzáková, Z; André, S; Gabius, H-J (Anatomia, histologia, embryologia, 2004)
Summary Multipotent stem cells (source for interfollicular epidermis, hairs and sebaceous glands) are localized in the bulge region of the outer root sheath of hair follicles, while stem cells giving rise to interfollicular epidermis reside in its basal. Using the multifunctional lectin galectin-1 as a marker to localize accessible binding sites in situ as a step to figure out galectin functionality in stem cells, we studied hair follicle-derived keratinocytes. Specific nuclear binding of galectin-1 associated with expression of DeltaNp63alpha, a potential marker of epidermal stem cells, was detected. Binding of chimera-type galectin-3 to a nuclear site was not found in parallel assays. During the process of ageing in culture when cells acquire properties of senescence, disappearance of the nuclear signal for galectin-1 binding was accompanied by a similar decrease of nuclear DeltaNp63alpha expression and increased binding of galectin-3 to the cell membrane, namely in regions of intercellular contacts. Expression of cytokeratin 10, a marker of the terminal differentiation was seen only in a small fraction of the cell population. These data extend the evidence for nuclear sites with galectin-1 reactivity in squamous epithelial cells, the expression of which is modulated upon senescence. Moreover, the results document the divergence of galectin-1 and -3 on the level of ligand selection in this cell type, underscoring the importance of the technical aspect to employ tissue lectins as probe and to perform a fingerprinting with several markers of the galectin family in parallel.
Keywords: galektin 3; Aging; Galectin 1; keratinocyty; Cell Differentiation; buněčná diferenciace; lidé; Cells, Cultured; Stem Cells; galektin 1; Galectin 3; keratiny; Keratinocytes; kmenové buňky; Keratins; stárnutí; kultivované buňky; Humans